Chemical compositions and biological activities of essential oils obtained from some Apiaceous and Lamiaceous plants collected in Thailand - Nawanit Thanaseelungkoon (2018)
© 2018 Asian Pacific Journal of Tropical Medicine Produced by Wolters Kluwer-Medknow. Objective: To determine the chemical composition, as well as the antioxidant, antityrosinase and antibacterial activities of essential oils obtained from some Apiaceous and Lamiaceous plants collected in Thailand. Methods: The essential oils of the specified spices and aromatic herbs were obtained by hydro-distillation, and their chemical constituents were analyzed by gas chromatography/mass spectrometry. Antioxidant assays were based on the scavenging effects of 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-Azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) free radicals as well as the lipid oxidation inhibition of ß-carotene bleaching by linoleic acid. Tyrosinase enzyme inhibition was evaluated by the dopachrome method. Broth microdilution technique was performed for the purposes of studying microbial growth inhibition against the isolated bacterial strains. Results: The essential oils of Elsholtzia stachyodes, Coleus amboinicus (I) and Trachyspermum ammi presented a high degree of potency in DPPH, ABTS and ß-carotene bleaching assays. The Trachyspermum ammi oil, which mainly contained thymol (49.04%) and p-cymene (22.06%), proved to be the most effective in terms of antibacterial activity. The major compositions of Coleus amboinicus (I) were carvacrol (51.57%), y-terpinene (18.04%) and p-cymene (7.81%); while thymol (43.76%) and y-terpinene (24.61%) were identified as the major components of Elsholtzia stachyodes oil, with p-cymene (6.73%) being identified as a minor constituent. Moreover, Cuminum cyminum oil containing cuminaldehyde (49.07%) and Elsholtzia communis oil composed with geranial (44.74%) and neral (35.27%) as the major components displayed a specific ability for the inhibition of the mushroom tyrosinase enzyme. Conclusions: The results indicated that these bioactive essential oils obtained from indigenous herbs are of significant interest as alternative raw materials in food, cosmetic and medicinal products.